Biochar adsorbent as well as preparation method and application thereof
By preparing iron-loaded biochar adsorbents, the problems of narrow pH application range and poor adsorption effect in the prior art are solved, and the efficient removal of pollutants in the garbage leachate is achieved, and the characteristics of low cost and simple process are achieved. .
Patent Information
- Application Number
- CN202411571082.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, when dealing with waste leachate, the pH of the adsorbent has a narrow range of application and poor adsorption effect. High temperatures during the preparation of biochar will damage its chemical adsorption properties.
Using a preparation method of loaded iron biochar adsorbent, a wide range of pH application and high adsorption capacity are prepared by mixing agricultural and forestry waste with diatomaceous earth and adding iron salts under specific pH conditions. adsorbent.
It has achieved efficient removal of pollutants such as TOC, total phosphorus, ammonia nitrogen in the garbage leachate, and the raw material cost of the adsorbent is low, the preparation process is simple, and it has the potential for large-scale application.
Smart Images

Figure CN119455892A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of pollution control, and in particular to a biochar adsorbent and a preparation method and application thereof. Background Art
[0002] Landfill leachate refers to a high-concentration organic wastewater that comes from the water contained in the garbage in the landfill, the rain and snow water entering the landfill, and other water, and passes through the garbage layer and the overburden layer. The water quality of landfill leachate is complex, generally showing high concentrations of organic matter, heavy metal salts, and ammonia nitrogen. For the removal of pollutants in landfill leachate, biological treatment is currently used, but the treatment efficiency is low, the working cycle is long, and the resistance to load impact is poor.
[0003] Adsorption is a potential wastewater treatment method with the characteristics of low operating cost and strong anti-interference ability. Traditional adsorbents include activated carbon, gel, polymer, clay mineral, porous metal oxide and other adsorption materials. Biochar is a porous carbon material produced by pyrolysis of organic raw materials under oxygen-limited or anaerobic conditions. It has the advantages of large specific surface area, strong adsorption capacity, good chemical stability and low economic cost. It is widely used in the field of adsorbent preparation. The raw materials for producing biochar can come from a variety of agricultural and urban organic wastes, such as straw, fruit shells, urban sludge, etc.
[0004] Biochar is mainly used in wastewater treatment technology to remove pollutants through adsorption. The adsorption capacity of biochar for pollutants is determined by its physical and chemical properties such as specific surface area, pore structure, surface groups and ion exchange capacity, which are related to the source of biochar raw materials and preparation conditions. Biochar prepared at high temperature has a higher carbon content, and volatile organic compounds in the raw materials are removed, which increases the pores and specific surface area. However, too high a temperature will destroy the surface groups of biochar, lose some chemical adsorption properties, and increase the energy consumption cost of production. Therefore, the best strategy needs to be selected for the source of biochar raw materials, preparation steps, parameters, etc. Based on this, selecting suitable biochar raw materials, selecting the optimal preparation scheme of biochar, and improving the adsorption capacity of biochar are the main research directions for the application of biochar in wastewater treatment technology.
[0005] Regarding biochar adsorption materials, Chinese patent document CN 106583422 B (application number 201611211684.5) discloses a process for solidifying high-salt arsenic slag. After pre-treatment, a biomass carbon arsenic stabilizer is added to the arsenic slag and stirred to react the arsenic in the arsenic slag to solidify the arsenic. The preparation method of the biomass carbon arsenic stabilizer comprises the following steps: step 1: placing an iron salt or a ferrous salt in deionized water and dissolving it to obtain an iron-containing solution, heating and stirring the iron-containing solution, and controlling the temperature of the iron-containing solution to 413K-433K, controlling the stirring rate to 60r / min-120r / min, and the stirring time to 30-60min, and obtaining an iron-based mother liquor after the stirring is completed; step 2: drying the plant waste material, placing the dried plant waste material in Stirring in a closed environment, and controlling the temperature in the closed environment to 473K-673K, and controlling the stirring time to 30min-60min, obtaining biomass carbon after the stirring is completed, and waiting for the biomass carbon to cool to 333K-343K, spraying the iron-based mother liquor on the biomass carbon, after spraying, placing the biomass carbon at room temperature for 180min-300min, and then washing the biomass carbon with deionized water, and drying the biomass carbon after washing to obtain iron-containing biomass carbon; Step three: adding calcium-containing filler to the iron-containing biomass carbon and mixing and stirring for 30min-60min to obtain a biomass carbon arsenic stabilizer.
[0006] Chinese patent document CN 117417020 A (application number 202311444460.9) discloses a method for preparing a water treatment material for removing and disinfecting pollutants from domestic grey water. The method uses agricultural biomass waste charcoal as a carrier, and generates a biochar-loaded magnesium peroxide ferrate product (MgFe2O4-MgO2-FeO4) through high-temperature pyrolysis and subsequent H2O2 oxidation under the condition of excessive divalent magnesium salt and trivalent iron salt ratio. The biochar and MgFe2O4 components contained in the biochar have good adsorption and chemical precipitation properties for nitrogen, phosphorus and heavy metals in water. At the same time, the H2O2 slowly released by the MgO2-FeO4 peroxide component in the material can be effectively activated to generate OH•, thereby achieving the oxidative removal of organic matter and pathogenic bacteria in the grey water. The material can effectively achieve the simultaneous removal of organic pollutants, heavy metals and pathogenic bacteria in domestic grey water.
[0007] In addition, Chinese patent document CN 116618015 A (application number 202310571602.1) discloses a soil remediation agent for treating heavy metal pollution, the preparation method of which comprises the following steps: (1) heat-treating sepiolite to obtain heat-treated sepiolite; (2) acid-treating the biomass, then rinsing with deionized water until the solution is neutral, and drying in a vacuum oven to obtain product A, ultrasonically dispersing product A, iron salt, cerium salt, yttrium salt, copper salt and manganese salt in methanol to obtain solution B, dispersing dimethylimidazole in methanol into solution C, and then adding solution C to solution B, mixing, stirring, filtering, washing, and vacuum drying to obtain product D; (3) mechanically mixing the heat-treated sepiolite obtained in step (1), product D obtained in step (2) and diatomaceous earth, heat-treating, cooling to room temperature, and obtaining a remediation agent. Summary of the invention
[0008] The technical problem to be solved by the present invention is to provide a biochar adsorbent with a wide pH application range and good adsorption effect, and a preparation method and application thereof.
[0009] The technical solution to achieve the first object of the present invention is a method for preparing a biochar adsorbent, comprising the following steps: ① The agricultural and forestry waste is crushed, washed, dried, soaked and degreased, and dried to obtain defatted biomass materials for standby use.
[0010] ② The defatted biomass material obtained in step ① is mixed with diatomaceous earth in a mass ratio of 1.2 to 1.8:1, and deionized water is added to form a mixture; sodium bicarbonate is added to the mixture for activation; then an iron salt solution is added; the pH value of the mixture is adjusted to 9 to 10 with a sodium hydroxide solution, and then stirred for 3 to 4 hours.
[0011] ③ Filter the material after stirring in step ②, dry the obtained solid to obtain an iron-carbon complex. Pyrolyze the iron-carbon complex at 600-800° C. for 2-2.5 hours under a nitrogen atmosphere to obtain an iron-loaded biochar adsorbent.
[0012] In the above step ①, the agricultural and forestry waste is one of Gorgon fruit shells, oil tea fruit shells, corn stalks, and coffee grounds.
[0013] In the above step ①, the agricultural and forestry waste powder is immersed in an organic solvent for degreasing, and the organic solvent is one or a mixed solvent of more than one of toluene, xylene, methanol, ethanol, acetone and hexane.
[0014] In the above step ①, the amount of organic solvent used for degreasing 10 g of agricultural and forestry waste powder is 80 to 120 mL.
[0015] In the above step ②, the amount of deionized water used is 20% to 25% of the total weight of the defatted biomass material and diatomaceous earth.
[0016] In the further step ②, the iron salt solution added to the mixture is a divalent iron salt solution or a trivalent iron salt solution. The iron salt solution is selected from trivalent iron salts such as ferric chloride, ferric nitrate, and ferric sulfate, and divalent iron salt solutions such as ferrous chloride, ferrous sulfate, and ferrous nitrate.
[0017] In step ②, after adding iron salt to the mixture, the mass ratio of iron source to carbon source is 2:1 to 5:1.
[0018] Optionally, in step ②, when sodium bicarbonate is added for activation, 800 mL of 1.8-2.5 mol / L sodium bicarbonate solution is added for activation for every 60-100 g of the mixture of gorgon shells and diatomaceous earth.
[0019] The technical solution for achieving the second object of the present invention is a biochar adsorbent prepared by the method as described above.
[0020] The technical solution for achieving the third object of the present invention is the use of a biochar adsorbent prepared by the method as described above in treating landfill leachate.
[0021] Optionally, biochar adsorbent is added to the landfill leachate to remove pollutants, the dosage of the iron-loaded biochar adsorbent is 1 to 10 g / L, the adsorption time is 1 to 2 hours, the temperature during the adsorption process is 20 to 40°C; the pH value of the landfill leachate is 5 to 11, preferably 7 to 9.
[0022] The present invention has positive effects: (1) The present invention provides an iron-loaded biochar adsorbent that can be used to treat landfill leachate and to treat wastewater by iron-carbon micro-electrolysis. The adsorbent retains the excellent porosity, specific surface area and rich surface groups of agricultural and forestry waste such as Gorgon shell biomass raw materials, defatted to remove inactive substances, mixed with diatomaceous earth and activated to improve adsorption performance, and loaded with iron-containing compounds so that the material obtains more adsorption sites. The adsorbent prepared according to the method of the present invention has a wide pH application range (5-11) and has a high removal rate of TOC, total phosphorus and ammonia nitrogen in landfill leachate.
[0023] (2) The raw material cost of the adsorbent of the present invention is low, the preparation process is simple, and it realizes the recycling of agricultural and forestry wastes, and has the potential for large-scale application.
[0024] (3) The adsorbent of the present invention can be further processed after adsorption to prepare a carbon-based soil slow-release fertilizer containing nitrogen and phosphorus nutrients, thereby taking into account both the effective removal of pollutants in wastewater and the sustainable utilization of non-renewable resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the preparation route map of Example 1.
[0026] Figure 2 This is the SEM image of the raw material of Gorgon fruit shell.
[0027] Figure 3 This is the SEM image of the iron-carbon complex in Example 1.
[0028] Figure 4 This is the EDS energy spectrum atomic ratio diagram of the iron-carbon complex in Example 1.
[0029] Figure 5 The SEM image of the adsorbent prepared in Example 1 is used to characterize its morphology.
[0030] Figure 6 This is the SEM image of the iron-carbon complex in Example 2.
[0031] Figure 7 This is the EDS energy spectrum atomic ratio diagram of the iron-carbon complex in Example 2.
[0032] Figure 8 The following is a SEM image showing the morphology of the adsorbent prepared in Example 2.
[0033] Fig. 9 The following is a SEM image showing the morphology of the adsorbent prepared in Example 3.
[0034] Fig.10 The following is a SEM image showing the morphology of the adsorbent prepared in Example 4. DETAILED DESCRIPTION
[0035] Introduced below are some of the multiple possible embodiments of the present invention, which are intended to provide a basic understanding of the present invention, and are not intended to confirm the key or decisive elements of the present invention or to limit the scope of protection. It is easy to understand that according to the technical solution of the present invention, without changing the essential spirit of the present invention, a person of ordinary skill in the art can propose other mutually replaceable implementations. Therefore, the following specific embodiments are only exemplary descriptions of the technical solution of the present invention, and should not be regarded as the whole of the present invention or as a limitation or restriction to the technical solution of the present invention.
[0036] (Example 1) See Figure 1 The biochar adsorbent of this embodiment is prepared according to the following steps: ① Take the Euryale shell (SEM picture see Figure 2 ) is crushed, sieved through a 100-200 mesh (150 mesh in this embodiment), washed with clean water, dried at 60°C, and then soaked in a mixed solution of toluene-ethanol (volume ratio 1:1) for 20-24 hours (22 hours in this embodiment) for degreasing, and air-cooled and dried for 24 hours to obtain a defatted biomass material for standby use. The defatted biomass material is sealed and dried for storage.
[0037] During defatting, 80 to 120 mL (100 mL in this embodiment) of the mixed solution is used for every 10 g of Gorgon fruit shell powder.
[0038] ② The defatted biomass material (Gorgon fruit shell) obtained in step ① is mixed with diatomaceous earth in a mass ratio of 1.5:1, and deionized water is added to obtain a mixture; the amount of deionized water used is 20% to 25% of the total weight of the defatted biomass material (Gorgon fruit shell) and diatomaceous earth.
[0039] 1.8-2.5 mol / L (2 mol / L in this embodiment) sodium bicarbonate solution is added to the above mixture for activation; for every 60-100 g of the mixture of Euryale ferox shell and diatomaceous earth, 800 mL of 1.8-2.5 mol / L sodium bicarbonate solution is added for activation; for example, in this embodiment, for 80 g of the mixture of Euryale ferox shell and diatomaceous earth, 800 mL of 2 mol / L sodium bicarbonate solution is added for activation.
[0040] Then add 45g / L ferric chloride solution. After adding ferric chloride, the mass ratio of iron source to carbon source (Gorgon fruit shell) is 2:1-5:1 (2:1 in this embodiment); adjust the pH value of the mixture to 9-10 (9 in this embodiment) with 10% sodium hydroxide solution, and stir for 3-4h (3h in this embodiment). Use hydrochloric acid and sodium hydroxide to adjust the acidity and alkalinity.
[0041] The iron salt solution added in this embodiment is a ferric chloride solution. In addition, the iron salt solution can also be selected from ferric nitrate, ferric sulfate, and a divalent iron salt solution such as ferrous chloride, ferrous sulfate, and ferrous nitrate.
[0042] ③ Filter the material after stirring in step ②, and dry the obtained solid to obtain an iron-carbon complex. The SEM image of the iron-carbon complex is shown in Figure 3 , EDS spectrum atomic ratio diagram see Figure 4 .
[0043] The iron-carbon complex was pyrolyzed at 600°C for 2.5 h in a tubular furnace under a nitrogen atmosphere of 100 mL / min, and then taken out, washed, and dried to obtain an iron-loaded biochar adsorbent.
[0044] The SEM image of the prepared iron-loaded biochar adsorbent is shown in Figure 5 .
[0045] (Example 2) The preparation method of the biochar adsorbent of this embodiment is the same as that of embodiment 1 except that: In step ①, the euryale shell is crushed and passed through a 200 mesh sieve. The mixed solution used for degreasing is xylene-ethanol in a volume ratio of 1:1. The mixed solution used for every 10g of euryale shell powder is 120mL.
[0046] In step ③, the SEM image of the iron-carbon complex is shown in Figure 6 , EDS spectrum mass ratio diagram is shown in Figure 7 The iron-carbon complex was pyrolyzed at 650℃ for 2h. The SEM image of the obtained iron-loaded biochar adsorbent is shown in Figure 8 .
[0047] (Example 3) The preparation method of the biochar adsorbent of this embodiment is the same as that of embodiment 1 except that: In step ①, the euryale shell is crushed and passed through a 100 mesh sieve. The mixed solution used for degreasing is acetone-ethanol with a volume ratio of 1:0.8. The mixed solution used for every 10g of euryale shell powder is 80mL. The degreasing soaking time is 24h.
[0048] In step ②, the defatted biomass material and diatomaceous earth are mixed in a mass ratio of 1.6:1.
[0049] The amount of deionized water used is 20% of the total weight of the defatted biomass material and diatomaceous earth.
[0050] 45 g / L of ferrous sulfate solution was added to the mixture. After the addition of ferrous sulfate, the mass ratio of iron source to carbon source was 4:1.
[0051] In step ③, pyrolysis was carried out at 750° C. for 2 h under a nitrogen atmosphere at 80 mL / min.
[0052] The SEM image of the prepared iron-loaded biochar adsorbent is shown in Fig. 9 .
[0053] (Example 4) The preparation method of the biochar adsorbent of this embodiment is the same as that of embodiment 1 except that: In step ①, the mixed solution for degreasing is toluene-ethanol in a volume ratio of 1:1.1.
[0054] To the mixture was added 50 g / L of ferric sulfate solution.
[0055] The mixture was adjusted to pH 10 with sodium hydroxide and stirred for 4 h.
[0056] In step ③, pyrolysis is carried out at 800°C for 2h.
[0057] The SEM image of the prepared iron-loaded biochar adsorbent is shown in Fig.10 .
[0058] (Example 5) The preparation method of the biochar adsorbent of this embodiment is the same as that of embodiment 1 except that: In step ①, the mixed solution for degreasing is toluene-methanol in a volume ratio of 1:1.
[0059] The mixture was adjusted to pH 10 with sodium hydroxide and stirred for 3 h.
[0060] (Example 6) The preparation method of the biochar adsorbent of this embodiment is the same as that of embodiment 1 except that: In step ①, the crushed agricultural and forestry waste is camellia oleifera shell.
[0061] In addition to tea oil fruit shells, corn stalks and coffee grounds can also be used to prepare biochar adsorbents according to the above method.
[0062] (Application example 1, ammonia nitrogen removal) Test objects: A. Biochar adsorbent prepared in Example 1. B. Biochar. C. Biochar. D. Biochar.
[0063] The rest of the preparation method of biochar is the same as that of Example 1, except that: after the Euryale ferox shell is crushed, washed with clean water, and dried at 60°C, it is pyrolyzed at 600°C for 2.5 h in a tubular furnace under a nitrogen atmosphere of 100 mL / min to obtain biochar; 45 g / L ferric chloride solution is sprayed on the biochar and then ground to obtain iron-loaded biochar.
[0064] The rest of the preparation method of biochar is the same as that of Example 1, except that: in step ②, 45 g / L of ferric chloride solution is added to the defatted biomass material obtained in step ①; the pH value of the mixture is adjusted to 9 with sodium hydroxide solution, and stirred for 3 hours.
[0065] The rest of the preparation method of biochar is the same as that of Example 1, except that: in step ②, 45 g / L of ferric chloride solution is added to the defatted biomass material obtained in step ①; the pH value of the mixture is adjusted to 9 with sodium hydroxide solution, and stirred for 3 hours. In step ③, after the iron-carbon complex is pyrolyzed, it is cooled and taken out and mixed with diatomaceous earth, and the mass ratio of diatomaceous earth to Gorgon shell raw material is 1:1.5.
[0066] The laboratory simulated organic wastewater containing ammonia nitrogen, with an ammonia nitrogen concentration of 100 mg / L.
[0067] The adsorption conditions are as follows: the dosage of the adsorbent in the simulated organic wastewater containing ammonia nitrogen is 1.5 g / L, the temperature is 25°C, the pH of the wastewater is adjusted to 9, and stirring is performed for 1.5 hours.
[0068] Removal effect: A: The ammonia nitrogen removal rate reached 88.27%, and the equilibrium adsorption capacity Qe was 58.85 mg / g.
[0069] B: The ammonia nitrogen removal rate reached 45.2%, and the equilibrium adsorption capacity Qe was 30.13 mg / g.
[0070] C: The ammonia nitrogen removal rate reached 52.3%, and the equilibrium adsorption capacity Qe was 34.87 mg / g.
[0071] D: The ammonia nitrogen removal rate reached 55.8%, and the equilibrium adsorption capacity Qe was 37.20 mg / g.
[0072] (Application example 2, TOC removal) Test objects: A. Biochar adsorbent prepared in Example 1. B. Biochar. C. Biochar. D. Biochar. (The preparation methods of B, C, and D are the same as those of Test Example 1).
[0073] The laboratory simulated landfill leachate had a total organic carbon concentration of 100 mg / L and a pH of 7.
[0074] The adsorption conditions were as follows: the dosage of adsorbent in the simulated landfill leachate was 1.5 g / L, the temperature was 25 °C, the pH was not adjusted, and stirring was performed for 1.5 h.
[0075] Removal effect: A: TOC removal rate is 53.4%.
[0076] B: TOC removal rate is 45.8%.
[0077] C: TOC removal rate is 48.9%.
[0078] D: TOC removal rate is 50.5%.
[0079] (Application example 3, total phosphorus removal) Test objects: A. Biochar adsorbent prepared in Example 1. B. Biochar. C. Biochar. D. Biochar. (The preparation methods of B, C, and D are the same as those of Test Example 1).
[0080] The laboratory simulated landfill leachate had a total phosphorus concentration of 100 mg / L and a pH of 7.
[0081] The adsorption conditions were as follows: the dosage of adsorbent in the simulated landfill leachate was 1.5 g / L, the temperature was 25 °C, the pH was not adjusted, and stirring was performed for 1.5 h.
[0082] Removal effect: A: The total phosphorus removal rate is 92.5%. The equilibrium adsorption capacity Qe is 61.67 mg / g.
[0083] B: Total phosphorus removal rate is 65.6%. The equilibrium adsorption capacity Qe is 43.73 mg / g.
[0084] C: Total phosphorus removal rate is 69.4%. The equilibrium adsorption capacity Qe is 46.27 mg / g.
[0085] D: Total phosphorus removal rate is 75.8%. The equilibrium adsorption capacity Qe is 50.53 mg / g.
[0086] (Application example 4, real landfill leachate adsorption test) Test objects: A. Biochar adsorbent prepared in Example 1. B. Biochar. C. Biochar. D. Biochar. (The preparation methods of B, C, and D are the same as those of Test Example 1).
[0087] The landfill leachate comes from fresh landfill leachate from a landfill transfer station, with TOC: 24500 mg / L, ammonia nitrogen: 1200 mg / L, total phosphorus: 150 mg / L, and pH=6.5.
[0088] The adsorption conditions were as follows: the adsorbent dosage in the landfill leachate was 20 g / L, the temperature was 25 °C, the pH was not adjusted, and the mixture was stirred for 1.5 h.
[0089] Removal effect: A: TOC removal rate is 45.8%; total phosphorus removal rate is 73.5%; ammonia nitrogen removal rate is 76.4%.
[0090] B: TOC removal rate is 22.6%; total phosphorus removal rate is 45.2%; ammonia nitrogen removal rate is 55.8%.
[0091] C: TOC removal rate is 32.8%; total phosphorus removal rate is 55.7%; ammonia nitrogen removal rate is 52.5%.
[0092] D: TOC removal rate is 42.7%; total phosphorus removal rate is 66.8%; ammonia nitrogen removal rate is 58.7%.
Claims
1. A method for preparing a biochar adsorbent, characterized in that The following steps are involved: ① Crush, wash and dry the agricultural and forestry waste, soak and degrease it, and dry it to obtain defatted biomass material for standby use; ② The defatted biomass material obtained in step ① is mixed with diatomaceous earth in a mass ratio of 1.2 to 1.8:1, and deionized water is added to form a mixture; sodium bicarbonate is added to the mixture for activation; then an iron salt solution is added; the pH value of the mixture is adjusted to 9 to 10 with a sodium hydroxide solution, and then stirred for 3 to 4 hours; ③ Filter the material after stirring in step ②, dry the obtained solid to obtain an iron-carbon complex; pyrolyze the iron-carbon complex at 600-800° C. for 2-2.5 hours under a nitrogen atmosphere to obtain an iron-loaded biochar adsorbent.
2. The method for preparing the biochar adsorbent according to claim 1, characterized in that: In step ①, the agricultural and forestry waste is one of gorgon fruit shells, oil tea fruit shells, corn stalks, and coffee grounds.
3. The method for preparing the biochar adsorbent according to claim 1, characterized in that: In step ①, the agricultural and forestry waste powder is immersed in an organic solvent for degreasing, and the organic solvent is one or a mixed solvent of more than one of toluene, xylene, methanol, ethanol, acetone and hexane.
4. The method for preparing the biochar adsorbent according to claim 3, characterized in that: In step ①, 80 to 120 mL of organic solvent is used for degreasing every 10 g of agricultural and forestry waste powder.
5. The method for preparing the biochar adsorbent according to claim 1, characterized in that: In step ②, the amount of deionized water used is 20% to 25% of the total weight of the defatted biomass material and diatomaceous earth.
6. The method for preparing the biochar adsorbent according to claim 1, characterized in that: In step ②, the iron salt solution added to the mixture is a divalent iron salt solution or a trivalent iron salt solution.
7. The method for preparing a biochar adsorbent according to claim 1, characterized in that: In step ②, after adding iron salt to the mixture, the mass ratio of iron source to carbon source is 2:1 to 5:
1.
8. The method for preparing a biochar adsorbent according to claim 1, characterized in that: In step ②, when sodium bicarbonate is added for activation, 800 mL of 1.8-2.5 mol / L sodium bicarbonate solution is added for activation for every 60-100 g of the mixture of euryale ferox shell and diatomaceous earth.
9. A biochar adsorbent prepared by the method according to claim 1.
10. Use of the biochar adsorbent prepared by the method according to claim 1 in treating landfill leachate.
Citation Information
Patent Citations
Novel biomass carbon-arsenic stabilizer preparation method and high-salt arsenic slag solidification process
CN106583422A
A solidification process for high-salt arsenic slag
CN106583422B
Soil remediation agent for treating heavy metal pollution and preparation method thereof
CN116618015A
Water treatment material for removing and disinfecting domestic grey water pollutants as well as preparation method and application of water treatment material
CN117417020A
Method for preparing magnetic biological carbon adsorbing material and usage thereof
CN101642699A